The Galician Imprint in Carmen Martín Gaite’s Work. From Literary Theory to Fictional Practice - Fuentes del Río, Mónica (Madrygal. Revista de Estudios Gallegos, 2020)
This paper analyzes the presence and influence of Galicia, its culture and its literature on the life and work of the writer Carmen Martín Gaite, in her literary theory and in her fictional practice, due to the Galician origins of her maternal family. In the first place, this aspect is studied in her reflections about the art of storytelling, contained in her essay and journalistic production; secondly, it is examined whether it is one of her cultural influences, present in her different creative facets; and, finally, it is investigated in her narrative, for example, as a thematic motif and as the location of some of her literary works. In addition, it is analyzed if her Galician ancestry implies her fascination with Portugal and its writers, who were very influential in the author, as well as the mutual connections between the Galician-Portuguese creators and her own work.